2019
DOI: 10.18805/lr-4035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urdbean (Vigna mungo) genotypes for mungbean yellow mosaic virus resistance through phenotypic reaction and genotypic analysis

Abstract: Mungbean yellow mosaic virus (MYMV) is a whitefly-transmitted major destructive virus affecting urdbean productivity in India. The objective of this research was to identify urdbean genotypes resistant against MYMV based on the phenotypic reaction and genotypic analysis. A total 48 urdbean genotypes were evaluated for resistance to MYMV by visual scoring of symptoms in the field under natural conditions. Disease severity was assessed using 0-9 rating scale, according to the mean disease score, the urdbean geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…These compounds also directly act as activators of protective enzymes like polyphenol oxidases. In the current study, it was observed that the genotypes with high phenols content showed less incidence of YMV and the above results were corroborated with the studies of Tamilzharasi et al (2020), Rajitha et al (2018) and Vannirajan et al (2019) in blackgram.…”
Section: Disease Scalesupporting
confidence: 91%
“…These compounds also directly act as activators of protective enzymes like polyphenol oxidases. In the current study, it was observed that the genotypes with high phenols content showed less incidence of YMV and the above results were corroborated with the studies of Tamilzharasi et al (2020), Rajitha et al (2018) and Vannirajan et al (2019) in blackgram.…”
Section: Disease Scalesupporting
confidence: 91%
“…Disease incidence was evaluated by following the standard disease rating scale [ 25 , 26 ]. Response of different mungbean lines was determined based on percent disease infestation and lines were scored by using recommended 0–5 arbitrary scale ( Table 1 ) at reproductive stage [ 27 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pyngrope et al (2015) screened 30 black gram genotypes using 12 SSR markers and from the study, PIC value ranged from 0.22 to 0.68 and three polymorphic markers CEDG 180, CEDG 139 and CEDG 279 were identified. Tamilzharasi et al, (2018) genotyped 48 black gram lines for YMV resistance and tagged the molecular markers CEDG180, ISSR8111357 and YMV1 FR. In the present investigation SSR marker CEDG 139 had shown the PIC value of 0.59 (Table 6).…”
Section: Resultsmentioning
confidence: 99%